2017
DOI: 10.1038/ncomms15296
|View full text |Cite
|
Sign up to set email alerts
|

Plastic roles of pericytes in the blood–retinal barrier

Abstract: The blood–retinal barrier (BRB) consists of tightly interconnected capillary endothelial cells covered with pericytes and glia, but the role of the pericytes in BRB regulation is not fully understood. Here, we show that platelet-derived growth factor (PDGF)-B/PDGF receptor beta (PDGFRβ) signalling is critical in formation and maturation of BRB through active recruitment of pericytes onto growing retinal vessels. Impaired pericyte recruitment to the vessels shows multiple vascular hallmarks of diabetic retinopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
214
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(229 citation statements)
references
References 73 publications
12
214
2
1
Order By: Relevance
“…Finally, the expression of Tie2 by pericytes has been fiercely debated in the past decades, with extensive characterization of Tie2 expression in cultured pericytes, but a lack of Tie2 expression noted in pericytes in vivo . However, recent evidence has shown that a pericytes‐specific knockout of Tie2 leads to dramatically altered vascular structure, paired with a demonstration of Tie2 acting as a potent pericyte chemokine in vitro, together suggesting that Tie2 signaling may serve an important role in pericyte function.…”
Section: Markers and Models To Study Microvascular Network Architecturementioning
confidence: 99%
“…Finally, the expression of Tie2 by pericytes has been fiercely debated in the past decades, with extensive characterization of Tie2 expression in cultured pericytes, but a lack of Tie2 expression noted in pericytes in vivo . However, recent evidence has shown that a pericytes‐specific knockout of Tie2 leads to dramatically altered vascular structure, paired with a demonstration of Tie2 acting as a potent pericyte chemokine in vitro, together suggesting that Tie2 signaling may serve an important role in pericyte function.…”
Section: Markers and Models To Study Microvascular Network Architecturementioning
confidence: 99%
“…Nonetheless, topographic differences of perivascular mural cells in the normal and diseased retina have not yet been evaluated. Meanwhile, pericyte loss as pathogenesis of DR has been extensively studied, including our group [12][13][14][15][16][17], and the arteriolar VSMC alteration of DR has been established [18]. However, the αSMA positive mural cell changes in the diabetic retinal capillaries have also not been well elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Whether an acute drop-out of pericytes in the adult organism leads to altered BBB permeability and alters the permissiveness of vasculature to leukocyte trafficking needs further studies. Pericyte ablation in adult mice using the Pdgfrb -Cre-Er T2 ; DTA mice was reported not to cause immediate BBB permeability changes in the retina and brain 24 ; however, pericyte loss in the brain was not assessed. Our unpublished data show that using the Pdgfrb -Cre-Er T2 ; DTA approach is not effective to deplete adult brain pericytes.…”
Section: Discussionmentioning
confidence: 99%